Riya' Perspective of Thematic Interpretation in the Qur'an - Hanna Salsabila; Eni Zulaiha (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the riya' perspective of the Qur'an. This study uses a qualitative method through literature study with an interpretation approach. The results and discussion of this study show that the understanding of riya' in the Qur'an based on thematic interpretation includes three things, namely riya' in prayer, in almsgiving, and riya' is the nature of the Quraysh infidels. This study concludes that riya 'is a commendable act that can eliminate the value of alms, the reward of prayer, and the reward of society. Therefore, Islam as confirmed by the Qur'an teaches to avoid the attitude of riya'. This study recommends that an in-depth study be carried out on other aspects of riya' in the perspective of the interpretation of the Qur'an to give birth to new things that are more solution.